Analisis Volatilitas Harga Dan Integrasi Vertikal Pasar Beras Di Indonesia - Triyandita Kusuma Harlianda; Gabriel Ivo Aveliano Kusuma Adi Valentino (Prodi Agribisnis, 2025)
Rice is the main staple food in Indonesia and is highly vulnerable to price fluctuations due to strong consumption dependence, quality issues, and the complexity of its supply chain. This study aims to analyze the volatility and vertical integration of medium and premium rice prices at the producer, wholesale, traditional market, and modern market levels. The data used are secondary data from the Ministry of Trade’s Market Monitoring System for Essential Goods (SP2KP) covering the period 2020–2024, analyzed quantitatively using the Coefficient of Variation (CV), ARCH/GARCH models, and VECM. The results show that all variables exhibit high persistence (greater than 0.75), indicating that price volatility tends to be long-lasting. Rice prices are highly vulnerable to short-term shocks such as weather, harvests, distribution, and import policies, as small disturbances can have prolonged effects without intervention. Producers are more reactive than consumers, so price shocks are transmitted more quickly at the producer level, while medium-grade consumers are relatively more stable due to distribution policies. The highest volatility is found at the retail level, whereas consumer prices are relatively more controlled, though instability has not been fully eliminated. Market integration analysis reveals both short-term and long-term linkages across price segments. These findings highlight the importance of stabilization measures, such as Bulog’s market operations, which should focus on mitigating short-term shocks to prevent prolonged impacts and to strengthen market integration in maintaining price stability and national food security.